A valoração das provas testemunhal e documental no processo do trabalho - Santoro, Gabriel Henrique (2016)
This essay’s object is to examine one of the current problems of the Labor Courts, which is the overrated value provided to witnessing evidence over documented evidence. Within this reality, we will study the essential principles related to evidence definition and the truth as part of a regular procedural environment. Nevertheless, we shall consider crucial evidence-related elements such as hierarchy levels and the over-exaggeration of witnesses' testimonies within labor proceedings. The essay’s key scope is to point out that the recurrent devaluation of documented evidence over witnesses shall create enormous disadvantages. In addition, such measure shall undermine the search for the actual truth within labor proceedings and deliver a sensation of insecurity to all the involved in a specific dispute, especially given that witnesses can be extremely fragile and cast shadow over reality. After all the necessary reflections, this essay shall suggest eventual mechanisms to analyze evidences produced before courts, targeting the preservation of the actual truth and the continuity of the confidence in the Courts of Law